Customer satisfaction guidelines for complaints handling in organizations (ISO 10002:2004, MOD) (Australian Standard. AS ISO ;, 2006)
"Provides guidance for the design and implementation of an effective and efficient complaints-handling process for all types of commercial and non-commercial activities." - page v.